Features of Educational Theory in Islam - Mohamed Abdulkarim Al-Ayasra (Sultan Qaboos University, 2007)
This study aimed at Identifying the basic features of Islamic educational theory. In order to achieve this aim, some procedures were followed. First, the Islamic educational theory was defined. Next, the views relating to Its existence were discussed. Then, its position as a sub- theory in the Islamic general system was explained. Alter that, the sources of Islamic educational theory were Identified and divided into two main categories: (i) The f'oced and genuine sources represented In the Holy Ouran and the prophet's teachings, sayings, and doings (Sunna). (2) Secondary sources which were connected with the history of lsiamic education, the opinions of Muslim thinkers, educationists and the findings of contemporary educational and academic studies. The study also iderrtlfled the features of Islamic educational theory, which distinguished it from other theories. The most important of these features is that it is a heavenly theory, from which many other characteristics are branched. Accordingly, some principles of Islamic educational theory were presented. The study concluded that Islamic educational theory is a unique theory. This is simply because It consists of some interwoven principles derived from the teaching of him. These principles guide, monitor, and control the practices of the educational process at all levels and stages. Thus, they are considered a theoretical and practical reflection of Islam In society, specifically in the field of education.